Helsingin yliopiston rehtori, professori, valtioneuvos Edvard Hjelt - Atelier Apollo
sisällön kuvaus: Edvard Hjelt
Keywords: tiedemiehet; professorit; hallintomiehet; solmiot; parta; Hjelt, Edvard Immanuel; Suomi, Helsinki, Helsinki